Eksistensi Angkutan Gerobak Sapi di Desa Pematang Karangan Hilir Kabupaten Tapin Tahun 1970-2021 - Jamaluddin, Jamaluddin; Anis, Mohamad Zaenal Arifin; Syaharuddin, Syaharuddin (Lambung Mangkurat University, 2023)
Traditional land transportation is transportation that uses the power of living things to move it, for example ox carts. However, with the development of the era, cart transportation is increasingly abandoned. Like in Pematang Karangan Hilir Village, where people still use traditional transportation for daily needs since 1970, however, until 2021, traditional transportation is slowly replaced by modern transportation in supporting the economy of the people of Pematang Karangan Hilir Village. The purpose of this study is to describe the development of ox cart transportation in Pematang Karangan Hilir Village in 1970-2021, ox cart transport ownership system, and the cause of ox cart transportation is no longer used by the community in Pematang Karangan Hilir Village. This research uses historical methods by going through four stages, namely heuristics, criticism, interpretation, and historiography. The results showed that the number of ox cart transportation from year to year was decreasing from 80 pieces in 1970 to the remaining 3 pieces in 2021, Ownership system of ox cart transportation both private and rental, and the transportation of ox carts was abandoned because there were engine-powered shuttles to the reduction of comudity transported using ox carts. The conclusion of this study is that ox cart transportation is no longer the main means of transportation to transport goods because it has been replaced by machine power transportation that makes it easier for the people of Pematang Karangan Hilir Village.